Treatment and prognosis of Scimitar syndrome: A retrospective analysis in a single center of East China - Wang, Kai; Xu, Xinyi; Liu, Tingliang; Gao, Wei; Guo, Ying (Frontiers in Cardiovascular Medicine, 2022)
Background: Scimitar syndrome is a rare congenital cardiovascular malformation; its optimal management remains controversial. This study aims to present the clinical experience of this disease in our center. Methods: We undertook a retrospective review of 34 patients with Scimitar syndrome documented at our institution between January 2013 and December 2018. The patients' clinical characteristics, management, and prognosis data were collected and analyzed. Results: 34 patients, including 16 males and 18 females, were enrolled with a median age at diagnosis of 7 months and a follow-up period of 22.5 months. The infantile form of Scimitar syndrome presents more tendency for pulmonary hypertension (PH), pulmonary vein stenosis (PVS), and mortality than the adult form. Of the 15 patients who underwent surgical correction of the Scimitar vein, 4 had post-operation PVS. There was no significant difference in the stenosis incidence between baffle repair and Scimitar vein reimplantation groups. Eight patients received interventional catheter therapy, including occlusion of aortopulmonary collateral arteries (APCs) and other intracardiac malformations, without the following surgery. The overall mortality rate was 20.5% (7 of 34) over the study period. High-risk factors of death included age at diagnosis (p=0.000), PH (p=0.007) and PVS (p=0.014). Conclusions: Infantile Scimitar syndrome needs intense suspicion for early diagnosis and multidisciplinary treatment. Interventional treatment of Scimitar syndrome alleviates pulmonary artery pressure and progression during infancy. Baffle repair and direct reimplantation of the Scimitar vein used in the surgical treatment of Scimitar syndrome are safe and have similar effects. Age at diagnosis, PH, and PVS are high-risk factors for death in Scimitar syndrome.